Effects of digital game-based learning as a tool for laparoscopy training in surgical nursing - Fatemeh Akbari HajiAbad; Fatemeh Keshmiri; Fatemeh Jabinian (PLoS ONE, 2026)
Background The present study aimed to (1) develop a digital game focusing on the roles of surgical nurses (scrub and circulator nurses) in laparoscopic surgeries, (2) conduct a randomized controlled trial (RCT) comparing this digital game-based learning (GBL) approach with a conventional teaching method, and (3) assess students’ reasoning and user satisfaction. Method This randomized controlled trial (RCT) was conducted at Shahid Sadoughi University of Medical Sciences. The study comprised three phases: development of the digital game titled ‘Co-Surgeon,’ implementation of the educational interventions, and evaluation of outcomes. The digital game aimed to enhance students’ understanding of laparoscopic surgeries and the specific roles of surgical nurses (circulator and scrub), focusing on tasks such as task recognition, laparoscopic instrument identification and utilization, procedural steps, and the development of clinical reasoning for selecting appropriate tools during common laparoscopic procedures. Fifty-seven surgical nursing students were randomly assigned to either an intervention group, which utilized digital game-based learning, or a control group, which received conventional lecture-based education. The digital GBL application included 40 distinct laparoscopic tools and equipment organized into 8 categories, 8 puzzles related to surgical nurse roles in abdominal laparoscopic surgeries, 15 Mayo stand setups, and 60 instrument identification puzzles. User satisfaction was measured via the Questionnaire for User Interface Satisfaction (QUIS), and students’ reasoning was assessed through the Key Feature (KF) examination. Data were summarized using descriptive statistics (mean, standard deviation, and percentage). Pearson correlation coefficient, independent t-test, and paired t-test were used for data analysis. Results The mean (SD) scores of students’ reasoning in the intervention group (19.51 ± 3.36) were significantly higher than those in the control group (13.92 ± 4.15). (p < 0.001), with a large educational effect size reported (Partial eta squared = 0.35). Student perception scores indicated a good level of satisfaction (184.85 ± 6.79). Conclusion The diverse and complex responsibilities of surgical nurses make it essential to enhance the learning outcomes for surgical nursing students. Implementing digital game-based learning can positively impact these outcomes. Therefore, it is recommended to incorporate digital games as a supplement in clinical education and workplace-based training.